Laborativa analyser av keramik från Hellum, Barmer och Kragelund - Lindahl, Andes (Hikuin, 2001)
Laboratory analyses of the potsherds from Hellum, Barmer and Kragelund By Anders Lindahl Laboratory analyses of the potsherds from Hellum, Barmer and Kragelund were performed in order to study the manufacturing techniques at the different sites. During the planning of the project it was suggested that the reconstructed pots to be fired in the kilns should not only have a shape resembling the original products, but also that the composition of their raw material should be as similar as possible to the medieval pots. Hence, the results of the laboratory analyses should be used as “recipes” for the manufacture of pottery from each kiln. These recipes would give suggestions of raw clays and temper material, amount and grain size of the temper as well as indications of forming techniques and firing conditions. Ten samples, three from each kiln and one raw lump of clay, were selected for thin-section analyses under a polarising microscope for the study of the composition of the ceramic ware. An additional 11 sherds from the Kragelund kiln were selected for the study of glazes and glazing methods. The results of the analyses indicate a great difference in the manufacture of vessels among the three kilns. The forming technique varies from modelling to wheel thrown and the tempering ranges from added crushed rock to added sand to the use of a naturally tempered finesandy clay. The tree kilns could represent either different stages in the development process of the handicraft or different modes of production for different markets.